P59 Risk factors for incident falls in older men and women: findings from the english longitudinal study of ageing. (September 2018) - Westbury, LD; Gale, CR; Cooper, C; Dennison, EM
Abstract : Background: Falls are a major cause of disability and death among older people, particularly women. Cross-sectional surveys suggest that some risk factors associated with a history of falls may be sex-specific but whether risk factors for incident falls differ between the sexes is unclear. This study investigated risk factors for incident falls and whether they differ between men and women. Methods: Participants were 3298 men and women (aged 60 years and over at Wave 4) who took part in the Waves 4–6 surveys of the English Longitudinal Study of Ageing. At Wave 4, they provided information on previous falls, sociodemographic, lifestyle, behavioural and medical factors, and had their physical and cognitive function assessed. Data on self-reported incident falls during the four-year follow-up period were collected at Waves 5 and 6. Relative risks (RR) for the association between baseline characteristics and incident falls were derived using sex-specific Poisson regression models with robust variance estimation. Factors associated with falling (p<0.20) were included in sex-specific mutually-adjusted models. Analyses were performed among men and women separately and relative risks were adjusted for previous falls before Wave 4. Results: Overall, 633 (41.8%) men and 863 (48.4%) women experienced an incident fall between Waves 4 and 6. In mutually-adjusted models, older age was the only factor associated with increased risk of incident falls in both sexes. Some factors were only predictive of falls in one sex, namely more depressive symptoms (RR (95% CI) 1.03 (1.01, 1.06)), incontinence (1.11 (1.00, 1.24)) and never having married in women (1.26 (1.03, 1.53)), and greater comorbidity (1.05 (1.00, 1.09)), higher levels of pain (1.11 (1.04, 1.18)) and poorer balance (1.25 (1.05, 1.49)) in men. Of these, only the relationships between pain, balance and comorbidity and falls risk differed significantly (p<0.05) by gender according to interaction tests. Conclusion: Older age was associated with increased risk of incident falls in both sexes. However, associations regarding pain, balance and comorbidity differed by gender. Strengths of the study include the large sample size and the fact that it is representative of the community-dwelling English population aged 60 years and over. However, one potential weakness is that there was no definition in the questionnaire of what constituted a fall. This research will inform the development of interventions to reduce the risk of falls among older people.